Disciplinary Sanctions for Police Officers According to Libyan Law (Comprehensive Journal of Science, 2026)
Disciplinary punishments are the administration is means of ensuring that its employees run public facilities regularly and steadily. As such, they are of an administrative nature. Disciplinary punishment is also considered a negative incentive in the public office because it includes a kind of deterrence and rebuke. Punishment makes the public employee fear the repetition of the mistake in order to avoid punishment. Thus, disciplinary punishment performs a restraining function to suppress any breach of the job. Therefore, disciplinary punishment is of a disciplinary nature. It is functional in addition to its administrative nature, and on top of that, it is a legal penalty that only arises in accordance with a law. If we take into account that the procedures are complex and take a long time, the administration often tends to evade disciplinary punishment by taking a measure of its own that achieves getting rid of the erring employee, without completing the disciplinary procedures. This is the meaning that we mean by the term “disguised disciplinary punishment.”  The opening words: disciplinary punishment, disguised punishment, member of the police force.